The Effect of IT-Based Applications on Students’ Speaking Skills in English Language Learning in Rural South East Sulawesi - Nurul Aisyah Arif; Sam Hermansyah; Maulina; Sufrianti Purnama (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
The integration of Information Technology (IT)-based applications in English language teaching has gained significant attention as a means to enhance students’ speaking skills, particularly in EFL contexts within rural areas. This study aimed to examine the effect of IT-based applications on the speaking skills of junior high school students in Rural Southeast Sulawesi. A quasi-experimental design was employed involving 82 students from grade VIII (44 students across two classes) and grade IX (38 students across two classes). The experimental group utilized various IT-based applications for interactive speaking practice, while the control group received conventional teacher-cantered instruction. Data were collected through pre-test and post-test speaking assessments and analysed using paired sample t-tests and independent sample t-tests. The findings revealed a statistically significant improvement in the speaking skills of students in the experimental group compared to the control group (p < 0.05), particularly in fluency, pronunciation, vocabulary, and grammatical accuracy. These results indicate that IT-based applications can effectively support the development of English-speaking proficiency among students in rural Indonesian schools. The study recommends the integration of technology-enhanced learning tools in the English curriculum to foster more engaging and effective language learning experiences.